2022
DOI: 10.3389/fcell.2022.1005681
|View full text |Cite
|
Sign up to set email alerts
|

Roles of osteoprotegerin in endocrine and metabolic disorders through receptor activator of nuclear factor kappa-B ligand/receptor activator of nuclear factor kappa-B signaling

Abstract: Endocrine and metabolic diseases show increasing incidence and high treatment costs worldwide. Due to the complexity of their etiology and mechanism, therapeutic strategies are still lacking. Osteoprotegerin (OPG), a member of the tumor necrosis factor receptor superfamily, appears to be a potential candidate for the treatment of these diseases. Studies based on clinical analysis and rodent animal models reveal the roles of OPG in various endocrine and metabolic processes or disorders, such as bone remodeling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…RANKL, also known as tumor necrosis factor ligand superfamily member 11 (Tnfsf11), secreted predominantly by osteoblasts, has been identified as a fundamental regulator of bone remodeling and an important factor connecting bone and energy metabolism [ 18 , 34 ]. Consistent with our findings, several studies have confirmed the relationship between RANKL and other metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…RANKL, also known as tumor necrosis factor ligand superfamily member 11 (Tnfsf11), secreted predominantly by osteoblasts, has been identified as a fundamental regulator of bone remodeling and an important factor connecting bone and energy metabolism [ 18 , 34 ]. Consistent with our findings, several studies have confirmed the relationship between RANKL and other metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge on these paracrine mechanisms focuses on the β cell dysfunction driven by the tumor-secreted products: exosomes are released from pancreatic neoplastic cells, which, in turn, deliver adrenomedullin to β cells and induce oxidative stress and cell death [25,26]. Another molecule of interest is represented by osteoprotegerin (OPG), a member of the TNF receptor super-family that has been shown to affect glucose homeostasis; while OPG levels are increased in patients with both type 1 and type 2 diabetes, compared to controls [27], Shi et al showed that OPG levels are increased in patients with NOD associated with PDAC as compared to patients suffering from type 2 DM, suggesting the potential benefit of this peptide as a biomarker for diagnosing NOD related to pancreatic cancer [28]. Moreover, the paracrine mechanism of DM in PDAC is also supported by surgical series: there is evidence that glycemic control can improve after subtotal pancreatectomy for pancreatic cancer, despite a reduction in insulin secretion, as revealed by Permert et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that DEHP shows obvious reproductive toxicity (Zhang et al, 2020) and results in much more problems, such as ovulation disorders, precocious puberty, and abnormal pregnancy. Endocrine and metabolic disorders have become risk factors for pregnancy complications, diabetes, and obesity (Huang et al, 2020;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that DEHP shows obvious reproductive toxicity (Zhang et al, 2020) and results in much more problems, such as ovulation disorders, precocious puberty, and abnormal pregnancy. Endocrine and metabolic disorders have become risk factors for pregnancy complications, diabetes, and obesity (Huang et al, 2020;Zhang et al, 2022).According to DOHaD theory, which is based on an epidemiological study about low birth weight and malnutrition (Barker, 2007), the effects of exposure before and during pregnancy would be reflected in the health status of offspring. If it is affected in the period of early life, it will interfere with the original growth process, resulting in incorrect coding and expression The DOHaD theory is now widely used in research on diseases, especially chronic diseases.…”
mentioning
confidence: 99%